Situación actual de la comercialización del cultivo de Sandía (Citrullus lamatus L.), en el cantón Babahoyo, Provincia de Los Ríos - Averos Hidalgo, Edison Barbarito (2020)
The present work of the practical component of the complexive examination was carried out in order to analyze the current situation of the commercialization of the Watermelon crop (Citrullus lamatus L.), in the Babahoyo canton, Los Ríos Province, for which the parameters involved were described , such as the importance of cultivation in our country, its nutritional value, production, profitability of the cultivation and possible marketing channels. In addition, the organizational structure of the producers, the standards of compliance with quality controls in international markets, the financing plans available to the producers, as well as the lack of advice and preparation that limit timely knowledge and progress were analyzed. of the families that depend on this important item within the country's economy.